Congenital disorder of glycosylation caused by starting site-specific variant in syntaxin-5 - Peter T. A. Linders; Eveline C. F. Gerretsen; Angel Ashikov; Mari-Anne Vals; Rinse de Boer; Natalia H. Revelo; Richard Arts; Melissa Baerenfaenger; Fokje Zijlstra; Karin Huijben; Kimiyo Raymond; Kai Muru; et al. (Nature Communications, 2021)
Mutations in genes critical for proper intra-Golgi transport can cause human syndromes due to defects in glycosylation of proteins. Here, the authors identify a human variant of Syntaxin-5 that causes fatal multisystem disease and mislocalization of glycosyltransferases due to altered Golgi transport.